1878 S.C. Acts 724, No. 602 - (:unkn) unknown (General Publisher, 1878)
It shall not be lawful for any person on the Counties of Horry, Marion, Darlington, Clarendon, Chesterfield, Georgetown, Marlboro, and Williamsburg to fish with nets or gigs, or set traps, or shoot fish with any kind of gun, in any of the fresh water rivers, creeks, lakes or other streams in said Counties, between the first day of May and the first day of September in any year hereafter.
--
Keywords: FISHING REGULATION